Comment on “A Radial Basis Function Collocation Method for Space-dependent Inverse Heat Problems, M. Nawaz Khan, I. Ahmad, H. Ahmad, J. Appl. Comput. Mech., 6, 2020, 1187-1199” - Saifudden Saif; Hossein Hosseinzadeh; Zeinab Sedaghatjoo (Journal of Applied and Computational Mechanics)
The purpose of this note is to address an error in the paper titled “A Radial Basis Function Collocation Method for Space-dependent Inverse Heat Problems,” published in the Journal of Applied and Computational Mechanics, 6, 2020, 1187-1199, which affects the numerical results presented therein. Consequently, we propose a numerical scheme to solve the inverse heat problem using the Radial Basis Functions Collocation Method. Then the paper is modified by this note.